Translating Great Russian Literature The Penguin Russian Classics - McAteer, Cathy (BASEES/Routledge Series on Russian and East European Studies, 2021)
Launched in 1950, Penguin's Russian Classics quickly progressed to include translations of many great works of Russian literature and the series came to be regarded by readers, both academic and general, as the de facto provider of classic Russian literature in English translation, the legacy of which reputation resonates right up to the present day. Through an analysis of the individuals involved, their agendas, and their socio-cultural context, this book, based on extensive original research, examines how Penguin's decisions and practices when translating and publishing the series played a significant role in deciding how Russian literature would be produced and marketed in English translation. As such the book represents a major contribution to Translation Studies, to the study of Russian literature, to book history and to the history of publishing.